Pengembangan Komposit Berbahan Ebonit Dengan Kandungan Sulfur 40 PHR Yang Diperkuat Serat Bambu Untuk Komponen Otomotif - Efendi, Rudy; , Joko Sedyono, ST, M.Eng, Ph.D (2017)
This study aims to determine the tensile strength, Izod impact, and hardness on the variation of the bamboo fiber content 0 gram, 272,72 gram, 520,83 gram of the composite matrix ebonite with a sulfur content of 40 phr. This study uses bamboo fiber as a reinforcement material and ebonite as a matrix. Fiber surface treatment process with NaOH 5% for 2 hours. Furthermore, the process of mixing natural rubber, fiber, and chemicals using two roll mill machine, then vulcanised using a hot press machine mold. Testing composites using ASTM D256-00 for Izod impact test, ASTM D638-02 for tensile test, ASTM D2240-81 for testing hardness. Resault impact study showed the highest price average on the composite ebonite with bamboo fiber content of 520,83 gram of 30.51 J / mm2, for the tensile test the higher fiber content, the higher tensile strength of the resulting composite is 14.8 MPa at ebonite with bamboo fiber content of 5520,83 gram while the lower the fiber content the greater the strain produced is 62.7% in ebonite without violence fiber and the highest average on bamboo fiber composite ebonite 520,83 gram 81.2 scale shore D.